A Comparative Analysis of Speech Errors in U.S. 2024 Presidential Debate - Kaonedy, Jesselyn; Nasution, Diantry Binarwaty Habibie; Sastia, May; Rangkuti, Rahmadsyah; Istiqomah, Istiqomah (Journal of English Language and Education, 2024)
This study focused on reviewing and analyzing the types of speech errors, comparing the frequency of such errors, and examining the reasons behind speech errors, as made by former President of the United States Donald Trump (DT) and Vice President Kamala Harris (KH) in the 2024 presidential election debate. Theory of speech error by Clark and Clark (1977) is used as the main guidance in the analysis. The debate, entitled "Harris vs Trump in the ABC News 2024 Presidential Debate", lasted 90 minutes. This study used a qualitative approach, this study analyzed the video of DT and KH, examining words, phrases, and sentences by transcribing their speeches. The results showed that DT committed more speech errors in total but less in types, while KH committed more types of speech errors and less errors in total. The causes of these speech errors were due to social factors, including anxiety and social pressure during the debate. Based on the amount of speech errors, KH sounds more promising than DT and has bigger possibilities to attract votes in the upcoming election.